A new species of the leafhopper genus Multiformis Li & Li (Hemiptera: Cicadellidae: Evacanthinae) from China - Li, Yu-Jian; Li, Zi-Zhong (Zootaxa, 2014)
The species of the Oriental leafhopper genus Multiformis Li & Li are reviewed. A new species, Multiformis ramosus sp. nov., from Yunnan Province, China is described and a key to all known species of Multiformis is provided.